Acute effects of whole-body vibration on elastic charge time in trained male athletes - Furlong, L.; Harrison, A. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Whole-body vibration (WBV) has been shown to increase jump height, power and strength but the mechanisms behind these changes are not fully understood. The aim of this study was to investigate the influence of WBV on elastic charge time, a surrogate measure of tendon and aponeurosis stiffness. 7 trained males were exposed to 10 vibrations at 30 Hz ± 4 mm with 60 seconds rest between each exposure. Pre and post-tests were conducted immediately, 5, 10, 15, 20, 30 and 40 minutes following vibration exposure. A significant increase in elastic charge times of both vibrated (p=0.004) and control (p=0.024) limbs suggest whole-body vibration decreases tendon and aponeurosis stiffness, possibly due to a warm-up effect of the lower limbs. Further study of the muscle stiffness response to vibration will improve understanding of the mechanisms behind performance improvements following vibration exposure.